2023
DOI: 10.1002/adts.202200687
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Catalytic Performance of C2N/GaN Heterostructure for Hydrogen Evolution Reaction by Doping

Abstract: In this work, a systematic theoretical study of the hydrogen evolution reaction (HER) catalytic activity of C2N/GaN heterostructure is carried out based on first principles. An indirect bandgap of 1.99 eV and type‐II band alignment are formed in the C2N/GaN heterostructure, which can facilitate the spatially efficient separation of photogenerated carrier pairs, and the band edge position matches the reduction potential of water. The catalytic performance of the HER reaction at the C and N sites is compared and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Moreover, it has been unraveled that the C 2 N exhibits superior visible-light response and chemical activity compared to the other graphene-like carbon nitride derivatives. 23,24 So far, C 2 N-based heterojunctions have been extensively investigated in various fields such as photovoltaics, electrocatalysis and photocatalysis, including C 2 N/GaN, 25 h-BN/C 2 N, 26 C 2 N/MoS 2 , 27 C 2 N/WS 2 , 28 Cs 3 Sb 2 I 9 /C 2 N, 29 C 2 N/antimonene 30 and so forth. It has been confirmed that the incorporation of the C 2 N into these heterojunctions significantly influences the bandgap, particularly affecting the electronic orbits at the bandgap edge.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been unraveled that the C 2 N exhibits superior visible-light response and chemical activity compared to the other graphene-like carbon nitride derivatives. 23,24 So far, C 2 N-based heterojunctions have been extensively investigated in various fields such as photovoltaics, electrocatalysis and photocatalysis, including C 2 N/GaN, 25 h-BN/C 2 N, 26 C 2 N/MoS 2 , 27 C 2 N/WS 2 , 28 Cs 3 Sb 2 I 9 /C 2 N, 29 C 2 N/antimonene 30 and so forth. It has been confirmed that the incorporation of the C 2 N into these heterojunctions significantly influences the bandgap, particularly affecting the electronic orbits at the bandgap edge.…”
Section: Introductionmentioning
confidence: 99%
“…Since 1979, when Inoue reported the ability of semiconductor photocatalysts to reduce CO 2 in water to organic compounds . Researchers have developed a number of semiconductor photocatalysts for photocatalysis, which can be categorized into the six categories below (1) metal oxides, such as TiO 2 , , ZnO; , (2) metal sulfides, such as CdS, ZnS, ZnIn 2 S 4 ; (3) metal nitrides and phosphides, such as GaN, Ni 2 P; (4) layered metal hydroxides, such as NiAl-LDH, MgAl-LDH; (5) metal–organic framework materials (MOFs); and (6) nonmetallic semiconductors, such as g-C 3 N 4 . , …”
Section: Introductionmentioning
confidence: 99%